Stevens-Johnson syndrome and toxic epidermal necrolysis associated with immune checkpoint inhibitors: a systematic review - Zhou, Jia; Wang, Chuan-Peng; Li, Jun; Zhang, Han-Lin; He, Chun-Xia (Frontiers in Immunology, 2024)
Introduction Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare yet life-threatening adverse events associated with immune checkpoint inhibitors (ICIs). This systematic review synthesizes the current literature to elucidate the clinical characteristics and outcomes of patients with ICI-related SJS/TEN. Methods We conducted a thorough search across databases including Embase, Web of Science, Cochrane, MEDLINE, Scopus, and PubMed. Selection criteria focused on reports of SJS/TEN among cancer patients treated with ICIs, analyzing clinical manifestations, therapeutic interventions, and outcomes. Results Our analysis included 47 articles involving 50 patients with ICI-related SJS/TEN. The cohort had a mean age of 63 years, with a slight male predominance (54%). Most patients had melanoma or non-small cell lung cancer. SJS/TEN typically occurred early, with a median onset of 23 days post-ICI initiation. Treatment primarily involved systemic corticosteroids and intravenous immunoglobulins. The overall mortality rate was 20%, higher for TEN at 32%, with infections and tumor progression as leading causes. Median time from onset to death was 28 days. Survivors experienced a median re-epithelization time of 30 days, positively correlated with the extent of epidermal detachment (rs = 0.639, p = 0.009). Deceased patients exhibited a significantly higher proportion of TEN (90% vs. 48%, p = 0.029) and a larger epidermal detachment area (90% vs. 30% of the body surface area [BSA], p = 0.005) compared to survivors. The combination therapy group showed a higher proportion of TEN compared to corticosteroid monotherapy or non-corticosteroid therapy groups (72% vs. 29% and 50%, p = 0.01), with no significant differences in mortality or re-epithelization time. Dual ICI therapy resulted in a higher TEN rate than single therapy (100% vs. 50%, p = 0.028). Among single ICI therapies, the sintilimab-treated group trended towards a higher TEN rate (75% vs. 40-50%, p = 0.417), a larger detachment area (90% vs. 30-48% of BSA, p = 0.172), and a longer re-epithelization time (44 vs. 14-28 days, p = 0.036) compared to other ICI groups, while mortality rates remained similar. Conclusion ICI-related SJS/TEN substantially impacts patient outcomes. Prospective clinical trials are critically needed to further clarify the pathogenesis and optimize therapeutic regimens.